A Comparative Analysis of Fiqh Final Semester Assessment Scores Based on Learning Methods and Gender in Madrasah Aliyah - Anggi Nurmalita; Ubaidillah; Nur Aviana; Durratul Lutfiah Qaidah; Rian Zuangsyah; Dwi Puspitasari (The Future of Education Journal, 2026)
The choice of learning methods and the gender perspective are crucial topics in modern Islamic education, but their actual impact on standardized cognitive outcomes is frequently debated. This study aims to comparatively analyze the differences in Final Semester Assessment (PAS) scores for Fiqh subjects based on three learning methods (Demonstration, Mind Mapping, and Lecture) and gender. A quantitative approach with an ex post facto causal-comparative design was employed at MAN 2 Kota Bandung, involving a sample of 108 tenth-grade students selected via total sampling across three parallel classes. Data collection used documentation of objective PAS scores. Due to the violation of the normality assumption (Shapiro-Wilk and Kolmogorov-Smirnov p < 0.05), hypothesis testing was shifted to the non-parametric Median Test. The results revealed: (1) there is no significant difference in Fiqh PAS scores among students taught using Demonstration, Mind Mapping, and Lecture methods (Asymp. Sig. = 1.000 > 0.05), with all groups achieving an identical median score of 87.00; (2) there is no significant difference in Fiqh PAS scores based on gender (Asymp. Sig. = 0.452 > 0.05). Consequently, the initial hypothesis was rejected. This study concludes that within the context of written objective evaluations, conventional methods exhibit cognitive effectiveness equivalent to active methods for both male and female students at MAN 2 Kota Bandung.